2005
DOI: 10.1103/physrevlett.94.125510
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Brittle Metallic Glasses: Brittleness or Plasticity

Abstract: We report a brittle Mg-based bulk metallic glass which approaches the ideal brittle behavior. However, a dimple structure is observed at the fracture surface by high resolution scanning electron microscopy, indicating some type of "ductile" fracture mechanism in this very brittle glass. We also show, from the available data, a clear correlation between the fracture toughness and plastic process zone size for various glasses. The results indicate that the fracture in brittle metallic glassy materials might also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
268
1
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(314 citation statements)
references
References 29 publications
19
268
1
10
Order By: Relevance
“…While the shear response of amorphous solids has received a significant amount of attention in the theoretical physics and molecular simulation literature over the past decade [1-8], significantly less attention has been devoted to hydrostatic loading in such systems [9,10]. This omission appears significant since experimental studies in metallic glass (MG) and other amorphous solids reveal nanocavities [11,12] that form during or subsequent to deformation and strongly implicate cavitation in the physics of the fracture process zone, even when the fracture behavior is relatively brittle [13][14][15]. The importance of cavitation in fracture is supported by recent molecular dynamics (MD) simulations in glassy Cu 50 Zr 50 and Fe 80 P 20 [16].…”
mentioning
confidence: 99%
“…While the shear response of amorphous solids has received a significant amount of attention in the theoretical physics and molecular simulation literature over the past decade [1-8], significantly less attention has been devoted to hydrostatic loading in such systems [9,10]. This omission appears significant since experimental studies in metallic glass (MG) and other amorphous solids reveal nanocavities [11,12] that form during or subsequent to deformation and strongly implicate cavitation in the physics of the fracture process zone, even when the fracture behavior is relatively brittle [13][14][15]. The importance of cavitation in fracture is supported by recent molecular dynamics (MD) simulations in glassy Cu 50 Zr 50 and Fe 80 P 20 [16].…”
mentioning
confidence: 99%
“…However, the deformation behaviors observed for the x=3, 4 alloys are very different from those with x=1, 2. Flat facets and flutes with fatal cracks are observed on the fracture surface, as shown in Figure 4(d); these are generally features of brittle materials such as Mg-and Fe-based BMGs [24]. It can be concluded that the alloys have a transition from ductility to brittleness when the Sn content increases from 2 to 3 at.%.…”
Section: Resultsmentioning
confidence: 71%
“…Формирование полос сдвиговой деформации [35,36] приводит к появлению ступенек на боко-вой поверхности образца, что показано на рис. 4.…”
Section: рис 2 схематическое изображение полос сдвигаunclassified
“…В случае, когда сдвиг обусловлен релакса-цией упругой энергии образца, значительное по-вышение температуры может возникнуть в резуль-тате локализованного течения. Локальный нагрев в полосах сдвига, в зависимости от температуры, напряжения и скорости деформации, может сти-мулировать переход от неоднородной деформации образца под нагрузкой к однородному течению [35,40]. И тем не менее есть основания полагать, что значительный нагрев образца происходит толь-ко в местах концентрации полос сдвига -вблизи микротрещин или у поверхности разрушения [39].…”
Section: рис 2 схематическое изображение полос сдвигаunclassified
See 1 more Smart Citation